Patent protection for medicinal products – the negative aspects, alternatives - Puciato, Daniel; Łoś, Agnieszka (Polish Journal of Public Health, 2011)
Patent protection of pharmaceutical products is exceptio-nally extensive and results from a specific nature of goods to which it relates. Application of intellectual property rights protection is justified in this case by arguments based on rule of justice and positive results of patent protection. However the negative effects of intellectual property protection (including deceptive innovations, social costs related to monopoly position of patent bearing company, social costs related to temporary limitation of free use of new ideas and technologies, more difficult access to medications in deve-loping countries) make it necessary to consider solutions alternative to the existing patent system. This thesis provides a review and evaluation of the above solutions as far as possibilities of their implementation and elimination of problems with medication manufacturing and accessibility are concerned. Implications to modification of the existing patent system resulting from the carried out solution analysis are a summary of the thesis.